"Francesco Messina" Archaeological Collection (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2017)
With this paper the authors aim to illustrate the formation of and the sequence of events concerning Francesco Messina’s Archaeological Collection. The main point of the study concerns, in fact, the archival records, unpublished up to now, preserved at Messina Archives: these documents shed light on the person of Francesco Messina as a collector and provide important and useful elements to retrace the history of his Archaeological Collection. Besides a concise consideration about the bound between collected items and the artist’s work, a biographical sketch and a brief digression on the influence of classical art on Francesco Messina’s production complete the present paper, with the aim of putting into context the Collection and the reasons behind Messina’s collecting activity.
Keywords: Francesco Messina; collecting; collectibles; private collection; archaeology; corplastic